Glycogenic hepatopathy following attempted suicide by long‐acting insulin overdose in patient with type 1 diabetes. Issue 5 (25th May 2020) - Fujisaki, Noritomo; Kosaki, Yoshinori; Nojima, Tsuyoshi; Higaki, Taiki; Yamada, Taihei; Koga, Hitoshi; Gochi, Akira; Naito, Hiromichi; Nakao, Atsunori
Abstract: Patients with poorly controlled insulin‐dependent type 1 or type 2 diabetes rarely present with glycogenic hepatopathy, which is characterized by hepatomegaly and liver enzyme abnormalities. Glycogenic hepatopathy occurs as a consequence of excessive accumulation of glycogen in hepatocytes caused by insulin. We report a young male patient with type 1 diabetes mellitus who developed glycogenic hepatopathy following a suicide attempt by insulin overdose via subcutaneous injection. The patient's medication/nutrition compliance and adherence to insulin were poorly controlled due to comorbid schizophrenia. Our patient required a large amount of continuous glucose to maintain euglycemia for persistent intractable hypoglycemia induced by overdose of long‐acting insulin. On admission day 4, the patient presented elevated transaminases, hepatomegaly, and lactic acidosis. Computed tomography revealed swollen liver parenchyma with a diffusely high absorption. The patient gradually recovered without any medical intervention except for adequate control of blood sugar and was moved to a psychiatric ward on day 8 for schizophrenia management. This report may help emergency physicians be aware of the common symptoms, clinical course, and pathophysiology of glycogenic hepatopathy. Doctors should include glycogenic hepatopathy in the differential diagnosis of abnormal liver enzymes and hepatomegaly for those with poorly controlled insulin‐dependent diabetes mellitus or unstable blood sugar levels due to insulin overdose like our patient.